2016
DOI: 10.1002/14651858.cd009729.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Over the counter (OTC) artificial tear drops for dry eye syndrome

Abstract: Background-Over the counter (OTC) artificial tears historically have been the first line of treatment for dry eye syndrome and dry eye-related conditions like contact lens discomfort, yet currently we know little regarding the overall efficacy of individual, commercially available artificial tears. This review provides a much needed meta-analytical look at all randomized and quasi-randomized clinical trials that have analyzed head-to-head comparisons of OTC artificial tears. Objectives-To evaluate the effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
138
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(140 citation statements)
references
References 100 publications
(397 reference statements)
2
138
0
Order By: Relevance
“…Nelson 1988 found that an unpreserved artificial tear containing 0.1% sodium hyaluronate was effective in improving dry eye symptoms and led to significant improvement in mean tear film osmolarity, break-up times, and conjunctival and corneal staining scores. However, the use of artificial tears has some limitations (Pucker 2016). The composition of natural tears is complex; they consist of water, salts, hydrocarbons, proteins, and lipids for which artificial tears cannot exactly serve as a substitute (Dogru 2011; Quinto 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Nelson 1988 found that an unpreserved artificial tear containing 0.1% sodium hyaluronate was effective in improving dry eye symptoms and led to significant improvement in mean tear film osmolarity, break-up times, and conjunctival and corneal staining scores. However, the use of artificial tears has some limitations (Pucker 2016). The composition of natural tears is complex; they consist of water, salts, hydrocarbons, proteins, and lipids for which artificial tears cannot exactly serve as a substitute (Dogru 2011; Quinto 2008).…”
Section: Introductionmentioning
confidence: 99%
“…19 The review included 43 RCTs examining 3,497 patients with dry eye of various etiologies. The authors concluded that while over-the-counter artificial tears were generally safe, there was considerable uncertainty regarding the form of artificial tears that works best for treating dry eye symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…The uncertainty mainly arose from the included RCTs being too heterogeneous in terms of study characteristics, patient characteristics, and outcomes reported to allow the conduct of informative meta-analyses. 19 …”
Section: Resultsmentioning
confidence: 99%
“…The collection of these fluids presents the valuable advantage of being non-invasive (urine, saliva, sweat, tears…) or minimally invasive (blood), allowing for multiple collections and the collection of meaningful amounts for the analyses to be performed. On the other hand, these fluids also present challenges, such as the extremely high dynamic range of plasma or serum, where a dozen of proteins represent more than 90% of the protein content; the more laborious procedure to obtain pure blood cell specimens [81]; or the still not standardized collection of fluids like saliva, sweat or tears [82][83][84].…”
Section: Biomarker Discovery In Peripheral Fluidsmentioning
confidence: 99%